2015
DOI: 10.1038/mp.2014.167
|View full text |Cite|
|
Sign up to set email alerts
|

Daytime spikes in dopaminergic activity drive rapid mood-cycling in mice

Abstract: Disruptions in circadian rhythms and dopaminergic activity are involved in the pathophysiology of bipolar disorder, though their interaction remains unclear. Moreover, a lack of animal models that display spontaneous cycling between mood states has hindered our mechanistic understanding of mood switching. Here we find that mice with a mutation in the circadian Clock gene (ClockΔ19) exhibit rapid mood-cycling, with a profound manic-like phenotype emerging during the day following a period of euthymia at night. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 43 publications
(54 reference statements)
3
121
0
1
Order By: Relevance
“…A more recent study extended the role of Clock gene and the regulation of anxiety related behaviours. Clock mutant mice were found to exhibit rapid mood cycling across the light-dark cycle such that the Clock mutants exhibited robust manic-like behaviour compared to wild-type controls when tested in an open field-, forced swim- and sucrose-preference test during the day [294]. Furthermore Clock mutant mice exhibited robust increases in both daytime tyrosine hydroxylase expression and VTA DA neuron activity [294].…”
Section: Circadian/sleep Rhythm and Depressionmentioning
confidence: 99%
“…A more recent study extended the role of Clock gene and the regulation of anxiety related behaviours. Clock mutant mice were found to exhibit rapid mood cycling across the light-dark cycle such that the Clock mutants exhibited robust manic-like behaviour compared to wild-type controls when tested in an open field-, forced swim- and sucrose-preference test during the day [294]. Furthermore Clock mutant mice exhibited robust increases in both daytime tyrosine hydroxylase expression and VTA DA neuron activity [294].…”
Section: Circadian/sleep Rhythm and Depressionmentioning
confidence: 99%
“…Although the master circadian pacemaker in the suprachiasmatic nucleus (SCN) of the hypothalamus synchronizes rhythms throughout the brain and body, the genes that control circadian rhythms are expressed in nearly every cell (6). In recent years, it has become apparent that these genes serve important functions in specific brain regions, including the control of daily rhythms in neuronal activity and the response to environmental stimuli (7)(8)(9).…”
mentioning
confidence: 99%
“…Investigators in McClung's laboratory have demonstrated that clock mutant mice (ClockΔ19) also exhibit changes in moodrelated behaviors, but the region specificity of this effect was impossible to elucidate in these constitutive mutants (10). The observation that region-specific rhythms of clock gene expression correlate with depression-like behaviors by Logan et al (1) is an important step forward toward identifying brain areas where clock genes are associated with mood-related and depression-related behaviors and vice versa.…”
Section: Michael Verwey Sherin Al-safadi and Shimon Amirmentioning
confidence: 99%